Self-Concept, Expectations, and Meaning of Life: Sinergy That Determines Learning - Sevilla-Santo, Dora Esperanza (2021)
The study sought to identify the personal factors that constitute barriers to student learning in public high schools located in Yucatan. It was conducted under a quantitative paradigm, with a correlational scope. Participants were freshmen of the 2017-2018 school year (2599) and their teachers (163). The information was collected through a questionnaire applied to the students, who inquired about their self-concept, expectations, meaning of life, and school background. A script for the teacher’s focus groups was also used; it identified the barriers they face to persuade the students to learn. The analysis of the relationships was obtained using Pearson’s correlation coefficient, the study of indicators of each factor, and the analysis of the teachers’ discourse. The results show that, among the limitations of learning, there are the blockades that the students form when they fail to recognize their capacities, or when they devalue them (negative self-concept), as well as their lack of goals to direct their actions, causing a low commitment as they don’t find sense to the lessons (sense of life). This shows flaws in the implementation of the educational model by underestimating the training for life in favor of knowledge acquisition, highlighting the need to train the teaching staff in means of giving feedback, recognition of the student´s potential, and application of strategies that prepare for life, so they can be able to enrich the formative process from these elements.